The effect of origin of the gelatine and ageing on the secondary structure and water dissolution. (May 2017) - Duconseille, Anne; Wien, Frank; Audonnet, Fabrice; Traore, Amidou; Refregiers, Matthieu; Astruc, Thierry; Santé-Lhoutellier, Veronique
Abstract: Gelatin is used to make hard capsules and has to meet strict dissolution specifications to guarantee homogeneous drug delivery. The aging of gelatin induces a decrease of its dissolution rate due to the formation of intra- and intermolecular cross-links. Cross-link formation has shown to be dependent on the environmental conditions of production, such as temperature and humidity, and therefore on the geographic origin of production. Gelatin structure consists of an amorphous phase (coil structure) and a crystal phase (triple-helixes) and is very sensitive to environmental changes. The present work aims at understanding the role and effects of structural changes during aging on gelatin dissolution, taking into account the origin of production. The molecular structure of pig skin gelatins from three different production sites of the same company were studied by differential scanning calorimetry, synchrotron circular dichroism and 1 H nuclear magnetic resonance. It turned out that aging induced the melting of triple-helixes, an increase of random coils and, probably, β-turn conformations. The gelatin structure varied with the origin of production and thus affected the dissolution rate. Gelatins with non-compliant dissolution rates exhibited a higher amount of amorphous phase after aging than compliant gelatins. Although it was not possible to formulate any certain interpretation of the synchrotron circular dichroism results regarding gelatin dissolution, this technique is able to differentiate compliant dissolutions from non-compliant ones, even before gelatin aging. Graphical abstract: Highlights: During aging, the quantity of crystals and their stability under heating decreased. Aging allowed the rearrangement of the gelatin chains in trans conformation. Water mobility increased under aging conditions. The structural state of gelatin is linked to its dissolution rate. CD discriminate compliant and non-compliant dissolution rates prior to gelatin aging.